2018
DOI: 10.1111/jvs.12620
|View full text |Cite
|
Sign up to set email alerts
|

Changes in vegetation structure and fuel characteristics along post‐fire succession promote alternative stable states and positive fire–vegetation feedbacks

Abstract: Aims Structural and compositional changes along post‐fire succession modify plant community proneness to burn (flammability). The dominant regeneration strategies and life forms, and their interactions along post‐fire succession, modulate these changes by affecting density, amount and connectivity of fuels. Depending on how flammability evolves during post‐fire succession it may feed back negatively, neutrally or positively into fire probability and behaviour. Negative fire–vegetation feedbacks arise when comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 53 publications
(105 reference statements)
4
55
0
9
Order By: Relevance
“…Khalil et al, ). As we were only able to assess habitat properties once (summer 2010), it would be interesting to repeat this inventory and to study if successional changes, which are likely to be observed in the fire area (Chen, Vasiliauskas, Kayahara, & Ilisson, ; Engelmark, ; Tiribelli, Kitzberger, & Morales, ), have affected both vole density, species richness among small mammals, and PUUV prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Khalil et al, ). As we were only able to assess habitat properties once (summer 2010), it would be interesting to repeat this inventory and to study if successional changes, which are likely to be observed in the fire area (Chen, Vasiliauskas, Kayahara, & Ilisson, ; Engelmark, ; Tiribelli, Kitzberger, & Morales, ), have affected both vole density, species richness among small mammals, and PUUV prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…, Tiribelli et al. ), illustrating the potential for differences in tree size arising from variation in prior interval to strongly shape post‐fire woody debris dynamics. In contrast, woody debris dynamics are likely to be much less strongly influenced by time since fire and prior fire interval in communities dominated by epicormically resprouting trees.…”
Section: Introductionmentioning
confidence: 99%
“…, Tiribelli et al. ) experiencing stand‐replacement vegetation dynamics in response to fire, albeit with differences in the scale and timing of responses reflecting differences in ecosystem productivity, decomposition processes, and biotic interactions. Specific features of the model are illustrated with photographs from our South‐Western Australian obligate‐seeder eucalypt woodland study system, as is the parameterization of woody debris temporal dynamics (Figs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations